Ответы и объяснения

  • Участник Знаний
2013-04-02T17:56:28+00:00

1) (х-4)(4х+6)=(х-5)^2

     4x^2+6x-16x-24=x^2-10x+25

     4x^2-10x-24=x^2-10x+25

      4x^2-x^2-10x+10x-24-25=0

      3x^2-49=0

      3x^2=49

       x^2=49/3

              7

       x=--------

              √3

 

             7√3

       x=--------

                 3

2) 3х^2-6х

  ----------- = 4-2х          |*2

         2

     3x^2-6x=2(4-2x)

      3x^2-6x=8-4x

      3x^2-6x+4x-8=0

      3x^2-2x-8=0

           1+-√1+24

       x=--------------

                    3

             1+-5

        x=---------

                 3

        x=2

        x=-4/3

   Ответ:2, -4/3